Pengembangan Aplikasi Penyewaan Mobil Menggunakan Metode Prototyping dengan Online Payment Gateway Midtrans - Radig Gedhe Prihatmoko; Egia Rosi Subhiyakto (P3M Politeknik Negeri Cilacap, 2024)
Car rental has become one of the most profitable industries, as cars have become an essential means of transportation for various societal needs, such as family activities and work. Many car rental companies still rely on conventional methods for promotions and reservations. There is one car rental place whose rental and promotion system still uses WhatsApp chat and telephone or comes directly to the rental. A website-shaped system is crucial as a company platform to showcase available vehicles, enable online transactions for rentals, and facilitate easy and convenient payments. The development of this website involves prototyping with PHP and MySQL programming languages, and the payment system incorporates the Midtrans payment gateway. The system is tested using Blackbox and User Acceptance Testing (UAT). This website's development aims to simplify the booking process for customers and enhance the company's ability to manage vehicle data and payments efficiently. Following the system's construction, testing is conducted, with the results of the UAT indicating a user satisfaction score of 90.8%. Based on the evaluation, the majority of users strongly agree with the developed application.